Total gastrectomy is a typical highly specialized procedure - Wroński, Konrad (Contemporary Oncology/Współczesna Onkologia, 2007)
Gastric cancer is one of the most common neoplasms in Poland. The only effective treatment of this neoplasm is surgery. The way the first operation is performed is one of the most significant prognostic factors in further procedures and also in the 5-year survival rate of patients. Extensive research conducted worldwide has revealed that in high-volume hospitals, that is, those in which the number of radical surgeries is large, there are fewer post-operative complications, lower post-operative death rate, shorter period of hospitalization, higher 2 and 5 year survival, as well as lower costs of hospital treatment. A review of the professional literature suggests that radical operations consisting of a complete or partial gastrectomy due to a neoplasm disease should be done in high-volume clinics.